Soil Development from Volcanic Ash Based on Different Pyroclastic Composition - Asmita Ahmad; Muchtar Salam Solle; Christianto Lopulisa (JOURNAL OF TROPICAL SOILS, 2019)
Potential volcano in several provinces in Indonesia played a significant role in the formation and quality of soil development. Soils that developed from the volcanic ashes often thought to contribute greatly to improve soil fertility, without regard to the nature and composition of the volcanic ash produced. Volcanic ash generated from the results in volcanic activity has a different composition, there are basaltic, andesitic and granitic, thereby affecting the process of formation and characteristics of the soil. The Objective of this study is to determine the soil development from different types of pyroclastic generated from Lokon volcano in North Sulawesi. The coordinates of research was in 1o 21' 18.0" N and 124o 49' 20.2"E. this research used ARL Quant X (EDXRF Analyzer) for X-Ray Fluorescence (XRF), Shimadzu XRD-7000 for  X-Ray Diffractometer (XRD), geology map (scale 1:250,000), topographic map (scale 1:50,000), XRD software, GIS 10.3 software. Soil analysis for texture, pH, C-Organic, and cation exchange capacity (CEC). There are two types of pyroclastic as the source of soil development from volcanic ash, there are; 1) basaltic pyroclastic with 43.26% Si02 that are resulted from the first magmatic eruption and 2) andesitic pyroclastic with 5.09% Si02 that are resulted from the late magmatic eruption. Basaltic pyroclastic contains Fe 37.63%, Al 11.35%, Ca 13.17% and Mg 5.69%, while andesitic pyroclastic contains Fe 38.35%, Al 6.87%, and Ca 8.61%. Rainfall ranges from 2000-3500 mm/yr helped the soil formation and influenced the character of the soil, such as sandy loam of soil texture, 3.08% of soil C-organic content, 23.24 cmol+/kg of CEC and 148.93 cmol+/kg of clay CEC. Clay minerals content of the soil is vermiculite, kaolinite and, halloysite. Cation supply from basaltic pyroclastic influenced the formation of vermiculite mineral, whereas andesitic pyroclastic more influences the formation of the kaolinite mineral. Formation of soil texture with a predominance of the sand fraction is more influenced by the type of andesitic pyroclastic that more resistant to weathering processes.Keywords: Soil; volcanic ash; pyroclastic; vermiculite; kaolinite